2003
DOI: 10.1038/sj.npp.1300005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the 5-HT2A Agonist Psilocybin on Mismatch Negativity Generation and AX-Continuous Performance Task: Implications for the Neuropharmacology of Cognitive Deficits in Schizophrenia

Abstract: Previously the NMDA (N-methyl-D-aspartate) receptor (NMDAR) antagonist ketamine was shown to disrupt generation of the auditory event-related potential (ERP) mismatch negativity (MMN) and the performance of an 'AX'-type continuous performance test (AX-CPT)Fmeasures of auditory and visual context-dependent information processingFin a similar manner as observed in schizophrenia. This placebo-controlled study investigated effects of the 5-HT 2A receptor agonist psilocybin on the same measures in 18 healthy volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(90 citation statements)
references
References 101 publications
(111 reference statements)
8
80
2
Order By: Relevance
“…Contrary to S-ketamine, the 5-HT 2A R agonist psilocybin neither reduced the MMN amplitude nor the MMN memory trace effect, which is consistent with a previously reported lack of psilocybin on MMN measured by a classical paradigm (Umbricht et al, 2003). Similarly, a recent MMN study with S-ketamine and the 5-HT 2A R agonist DMT showed that the frontal MMN was only affected by S-ketamine and not by DMT (Heekeren et al, 2008).…”
Section: S-ketamine-induced Cognitive Impairmentssupporting
confidence: 73%
See 1 more Smart Citation
“…Contrary to S-ketamine, the 5-HT 2A R agonist psilocybin neither reduced the MMN amplitude nor the MMN memory trace effect, which is consistent with a previously reported lack of psilocybin on MMN measured by a classical paradigm (Umbricht et al, 2003). Similarly, a recent MMN study with S-ketamine and the 5-HT 2A R agonist DMT showed that the frontal MMN was only affected by S-ketamine and not by DMT (Heekeren et al, 2008).…”
Section: S-ketamine-induced Cognitive Impairmentssupporting
confidence: 73%
“…Here, we followed previous studies of the roving paradigm (eg, Garrido et al, 2008) in focusing only on deviants preceded by at least 6 standards. Waveforms were mathematically referenced to an average-mastoid reference before peak detection, analogously analyzed as previous studies (Umbricht et al, 2000(Umbricht et al, , 2002(Umbricht et al, , 2003. Based on previous studies, a set of frontocentral (Fz, F3, and F4) and -temporal electrodes (TP7 and TP8) were preselected (Alho et al, 1996;Sato et al, 2000;Tiitinen et al, 1993;Waberski et al, 2001).…”
Section: Eeg/erp Recordingmentioning
confidence: 99%
“…The pattern of AX-CPT dysfunction observed in this study is thus consistent with the pattern predicted from NMDA models of the disorder. Finally, similar deficits in AX-CPT performance have been observed following administration of the 5-HT2A receptor agonist psilocybin to normal volunteers (Umbricht et al, 2003), suggesting that convergent dysfunction of multiple transmitter systems may conspire to disrupt prefrontal function in schizophrenia.…”
Section: Discussionmentioning
confidence: 65%
“…The NMDA antagonist ketamine for instance leads to an attenuation of the MMN, which is similar to that observed in schizophrenia, and induces disturbances in perception and cognitive functioning, resembling symptoms observed in this disease (Umbricht et al, 2000;KreitschmannAndermahr et al, 2001;Umbricht et al, 2002). On contrast, MMN was unaffected by the intake of the 5-HT 2A receptor agonist psilocybin, although psilocybin induces cognitive disturbances and models other psychotic behavior (Umbricht et al, 2003). Similarly, tryptophan depletion leading to generally decreased 5-HT levels affected only the latency of the neuromagnetic MMN (MMNm) but not its amplitude .…”
Section: Introductionmentioning
confidence: 85%